HISTOPATHOLOGICAL CHANGES OF THE ENDOMETRIUM IN PATIENTS WITH ABNORMAL UTERINE BLEEDING AND ASSOCIATION WITH SOME RISK FACTORS - Kocevska, Ana; Zafirov, Dimce; Petrusevska, Gordana; Skeparovska, Kristina; Stratrova, Slavica Subeska (Journal of Morphological Sciences; Vol 4 No 2 (2021): JMS, 2021)
Abnormal uterine bleeding is a complex gynecological problem, especially in the perimenopausal and postmenopausal period. Etiology may be organic (endometrial polyp, hyperplasia, myoma, endometrial atrophy, carcinoma) or non-organic (dysfunctional uterine bleeding). To analyze the histopathological findings of samples of fractionated explorative curettage in patients with abnormal uterine bleeding and to investigate certain risk factors for their occurrence (age, obesity, hypertension, diabetes). This was a prospective study comprising a total of 104 subjects. They were divided into two groups: 54 women in postmenopausal age and 50 in premenopausal age. The data were collected by interviewing and analyzing the findings from histopathological analyses of samples obtained by fractional explorative curettage. The following anamnestic data were analyzed: age, history of hypertension and diabetes. The study was performed in the Special Hospital for Gynecology and Obstetrics "Mother Theresa" - Chair. The most common pathological finding in both groups was endometrial polyp (in 39.5% of postmenopausal and 46.9% of premenopausal women). In 4 participants (5.7% of the total), endometrial adenocarcinoma was diagnosed. The mean age of patients was 57 years in the postmenopausal group and 43 years in the premenopausal group. The average BMI (Body Mass Index) was 33 in the postmenopausal group and 25 in the premenopausal group. Hypertension was detected in 64.8% of postmenopausal women and in 34% of premenopausal women. 13% of postmenopausal women were diagnosed with diabetes. It was detected in 12% of premenopausal women. Fractional explorative curettage is an important diagnostic procedure for prompt and timely diagnosis of premalignant and malignant changes of the female genital tract. We detected endometrial adenocarcinoma in 7,4% of the postmenopausal patients and in 4% of premenopausal patients with abnormal uterine bleeding. It is especially important to highlight obesity and hypertension as risk factors for abnormal uterine bleeding and endometrial pathology. Key words : abnormal bleeding, uterus, fractional explorative curettage  https://doi.org/10.55302/JMS2142066k